2019
DOI: 10.1371/journal.pone.0210703
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in emergency department visits and hospitalization rates for inflammatory bowel disease in the era of biologics

Abstract: BackgroundThe use of biologics in inflammatory bowel disease (IBD) has increased recently. However, studies on whether the proportion of IBD patient visits to the emergency department (ED) has decreased are scarce. We investigated the trends in IBD-related ED visits and hospitalization rates.MethodsMedical records of IBD-related visits to the ambulatory department (AD) and the ED of the Seoul National University Bundang Hospital in 2007, 2009, 2012, and 2014 were reviewed. Multiple-variable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
(22 reference statements)
0
19
1
Order By: Relevance
“…The impact of the introduction of biologic therapy on disease-related hospitalizations has been investigated in previous studies with inconsistent results. Comparable to the current study that showed a similar hospitalization rate before and after biologic therapy, several studies, mainly in the adult population, reported no change in the rates of IBD-related hospitalizations [ 20 , 38 ]. Other studies observed an increase in hospitalizations in the last two decades and an increased risk of hospitalization in patients treated with thiopurines, corticosteroids, and anti-TNF-α agents [ 22 , 39 ].…”
Section: Discussioncontrasting
confidence: 60%
“…The impact of the introduction of biologic therapy on disease-related hospitalizations has been investigated in previous studies with inconsistent results. Comparable to the current study that showed a similar hospitalization rate before and after biologic therapy, several studies, mainly in the adult population, reported no change in the rates of IBD-related hospitalizations [ 20 , 38 ]. Other studies observed an increase in hospitalizations in the last two decades and an increased risk of hospitalization in patients treated with thiopurines, corticosteroids, and anti-TNF-α agents [ 22 , 39 ].…”
Section: Discussioncontrasting
confidence: 60%
“…In the last two decades, the rates of IBD related admissions and IBD related surgeries declined significantly. Surprisingly, the number of IBD-related ED visits has numerically surged, but the proportion of IBD patients who needed ED care decreased [ 10 , 13 ]. This is an interesting phenomenon explained in part by the rise in IBD cases in some parts of the world and by the existence of a group of patients who tend to have recurrent visits to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that while young female patients tend to visit the ED more often [ 15 ], older and male patients are more likely to be admitted [ 12 , 13 ]. Smokers, highest income quartile patients, penetrative disease, and steroid exposure are also predictors of hospitalization [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations